2021
DOI: 10.1177/14680874211047743
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the outcomes of a single-cylinder CRDI engine operated by lemon peel oil under the influence of DTBP, rice husk nano additive and water injection

Abstract: In the search for an alternative energy source with lesser pollution for transportation needs, bio-oil, a denser and viscous fuel that needs a transesterification process, have been widely considered for diesel engines. However, these problems are solved by using low viscous biofuel, but this improvement also significantly leads to increased NOx emission. Hence this present study investigates the usage of a low viscous biofuel in the CRDI engine with measures to reduce NOx emission through water injection tech… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…The BTE is the ratio of the thermal power available in the fuel to the power that the engine delivers to the crankshaft (Panithasan & Venkadesan, 2023). The brake thermal efficiency was observed at the B30 proportion of the biodiesel blend at variable loads, shown in Figure 7.…”
Section: Brake Thermal Efficiency (Bte)mentioning
confidence: 99%
“…The BTE is the ratio of the thermal power available in the fuel to the power that the engine delivers to the crankshaft (Panithasan & Venkadesan, 2023). The brake thermal efficiency was observed at the B30 proportion of the biodiesel blend at variable loads, shown in Figure 7.…”
Section: Brake Thermal Efficiency (Bte)mentioning
confidence: 99%
“…This was similar to what some authors have found and might be attributed to a better atomisation of the fuel, better vaporisation and a reduction in the viscosity of the mixture. In addition, the presence of oxygen in the fuel helped it to burn more efficiently, increasing the BTE of the engine [34,35]. Some other authors have found the efficiency to decrease, attributing this to the negative effect of the lower cetane number of turpentine [36].…”
Section: Fuel Consumptionmentioning
confidence: 99%
“…Reduced BTE value of 8.9% indicates that 2% water influences other outputs and reduces NOx emission by 11%. 43…”
Section: Introductionmentioning
confidence: 99%
“…Reduced BTE value of 8.9% indicates that 2% water influences other outputs and reduces NOx emission by 11%. 43 There are several papers studied the effect of ethanol addition in gasoline engines. This paper covers the gab by investigation of ethanol blending with ethanol in mathematical model describing the combustion, performance and emissions of petrol engine.…”
Section: Introductionmentioning
confidence: 99%